Effect of 131I with and without artificial liver support system in patients with Graves’ disease and severe liver dysfunction: A retrospective study - Rao, Maohua; Wang, Yirui; Ren, Jianli; Chen, Yue; Zheng, Chenxi; Xiong, Yalan; Yan, Qingbo; Li, Shiying; Yuan, Gengbiao (Frontiers in Endocrinology, 2022)
OBJECTIVE:Treatment decision-making in Graves’ disease (GD) with severe liver dysfunction (LD) is a clinical challenge. This research was carried out to evaluate the effect of radioiodine (131I) with or without an artificial liver support system (ALSS) in GD patients with severe LD. METHODS: In total, 45 patients diagnosed with GD and severe LD were enrolled and allocated to two groups: patients treated with 131I alone (n=30) (Group A)and patients by a combination of 131I and ALSS (n=15)(Group B). Liver function, thyroid hormone concentrations, therapeutic efficacy, and the cost of treatment were compared between the two groups. RESULTS: Thyroid hormone concentrations were lower 2 weeks after 131I treatment, but no deterioration in liver function was identified. There was no statistically significant difference in the treatment efficacy between the two groups. The hospital stay, total cost, and daily cost were lower in patients treated with 131I alone than in those treated with 131I and an ALSS (p<0.05). CONCLUSION:The key point of treating GD patients with severe LD is to control the GD.131I is recommended as an effective and safe and should be applied as soon as possible once the diagnosis is clarified; however, when used in combination with an ALSS, there was no substantial improvement in therapeutic efficacy.